A facile approach for fabrication of mechanically strong graphene/polypyrrole films with large areal capacitance for supercapacitor applications. Issue 124 (30th November 2015) - Ge, Yu; Wang, Caiyun; Shu, Kewei; Zhao, Chen; Jia, Xiaoteng; Gambhir, Sanjeev; Wallace, Gordon G.
Abstract : Mechanically strong and flexible graphene/polypyrrole composite films with hierarchical structures are fabricated. They demonstrate very high areal capacitances. Abstract : Substantial progress has been made in free-standing flexible graphene-based films for flexible supercapacitors. However, there are limited reports on the areal capacitance of these electrodes, which is an important parameter for practical applications, especially in miniaturized electronic devices. Herein we report the facile fabrication of robust flexible graphene/polypyrrole nanoparticle films. PPy NPs act as the "spacer" between graphene layers creating hierarchical structures. This free-standing film shows excellent mechanical properties with a fracture strength of 16.89 MPa and Young's modulus of 11.77 MPa. The resulting film electrode delivers a large areal specific capacitance of 216 mF cm −2, which is higher or comparable to other graphene/conducting polymer composite films. Moreover, this composite film exhibits a high capacitance retention rate of 87% after 5000 charge/discharge cycles and a fast relaxation time constant of 2.51 s. These excellent properties all suggest their prospective use in flexible energy storage devices.